The cat in the hat - Seuss, Dr. (New York : Random House, 1985)
Two children sitting at home on a rainy day are visited by the Cat in the Hat, who shows them some tricks and games.
Originally published in 1957.
Wilson's Children, October 2010.
Book Links (A.L.A.), January 2007.
School Library Media Quarterly (A.A.A.L.), November 2006.
Library Journal, January 1999.
Booklist, August 1997.
Keywords: Cat in the Hat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Cat in the Hat (Fictitious character) -- Fiction; Cats -- Fiction; Stories in rhyme; Cats -- Poetry; Nonsense verses; Readers (Elementary)